Diagnostic test performance of the Mentzer index in evaluating Saudi children with microcytosis - AlQarni, Amani M.; Althumairi, Arwa; Alkaltham, Nourah K.; AlJishi, Samaa; Hakami, Amani Mohammed; Abdalla, Leena Mohamed Osman Ali; Alawi, Zahra Sayed Jalal; Alreedy, Abdullah H. (Frontiers in Medicine, 2024)
Background Anemia is a global public health concern, affecting both developing and industrialized countries at a rate of 39.8%. It is defined by low hemoglobin concentration, and anemia varies in severity based on age: <11 g/dL (6–59 months), <11.5 g/dL (5–11 years), and < 12 g/dL (12–14 years). Aim This study evaluates the Mentzer index’s reliability in differentiating iron deficiency anemia from the thalassemia trait. Methods A total of 434 children (≤16 years) with hemoglobin electrophoresis previously screened for microcytosis (MCV <80 FL) and an iron profile were included. Children with other hematological conditions were excluded. Results Out of 434 children, 181 were diagnosed with thalassemia, and 345 had iron deficiency anemia. The Mentzer index showed 74% sensitivity and 63% specificity for the beta-thalassemia trait, with 61% sensitivity and 36% specificity for iron deficiency anemia. The beta-thalassemia trait group had the highest negative predictive value (98%), while iron deficiency anemia had the highest positive predictive value (79%). Conclusion Our study, which is consistent with previous literature, suggests that the Mentzer index is not highly reliable in distinguishing iron deficiency anemia from the thalassemia trait among children in Saudi Arabia.